Tax Imposition And Legal Enforcement On The Digital Asset Of Non-Fungible Token (NFT) - Annisa Intan Dwitanti; Dian Puji Simatupang (Unram Law Review, 2022)
Non-Fungible Token (NFT) is a token on the blockchain network that is used as a token of authenticity in the ownership of digital work. Along with the development of NFT as one of the investment instruments in Indonesia, it certainly raises big questions in terms of taxation. The problems in this study include, how to regulate the imposition of taxes on digital NFT asset transactions and how to enforce the law if there is a taxpayer deviation from NFT digital asset transactions. This research method is qualitative and descriptive with a normative legal approach. The results of the study indicate that NFT digital assets do not have specific tax regulations in Indonesia, but in connection with the transaction being supported through cryptocurrency, the tax is imposed according to PMK Number 68/PMK.03/2022. In terms of law enforcement on tax payments on NFT digital asset transactions, administrative and criminal sanctions may be imposed in accordance with Law Number 28 of 2007 concerning General Provisions and Tax Procedures.